2009
DOI: 10.1088/0004-637x/693/2/1074
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Spectra From Doppler-Broadened Spectral Lines: Tests of the Velocity Channel Analysis and Velocity Coordinate Spectrum Techniques

Abstract: Turbulent motions induce Doppler shifts of observable emission and absorption lines motivating studies of turbulence using precision spectroscopy. We provide the numerical testing of the two most promising techniques, Velocity Channel Analysis (VCA) and Velocity Coordinate Spectrum (VCS). We obtain an expression for the shot noise that the discretization of the numerical data entails and successfully test it. We show that the numerical resolution required for recovering the underlying turbulent spectrum from o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 35 publications
0
73
0
Order By: Relevance
“…The VCS technique, which as been numerically tested in Chepurnov & Lazarian (2009), has a bright future ahead in terms of measuring the properties of turbulence in a number of interesting environments. The technique thus far has been applied primarily in the context of 21 cm data but there is no reason not to apply it to the wealth of molecular line tracers such as CO, as was done in Padoan et al (2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VCS technique, which as been numerically tested in Chepurnov & Lazarian (2009), has a bright future ahead in terms of measuring the properties of turbulence in a number of interesting environments. The technique thus far has been applied primarily in the context of 21 cm data but there is no reason not to apply it to the wealth of molecular line tracers such as CO, as was done in Padoan et al (2009).…”
Section: Discussionmentioning
confidence: 99%
“…This is because the VCA technique is concerned with taking the spatial power spectrum of the two-dimensional (2D) slices of PPV while the VCS studies the fluctuations of PPV intensities along the velocity coordinate of the PPV cube. Both techniques have been applied to multi-wavelength observations as well as having undergone numerical tests (Stanimirović & Lazarian 2001;Chepurnov & Lazarian 2009;.…”
Section: Introductionmentioning
confidence: 99%
“…We examined the changes in the distribution of the dendrogram as we vary the threshold parameter δ. This is analogous to changing the corresponding threshold parameter in other techniques that rely on contouring thresholds, e.g., in the Genus analysis (see Chepurnov & Lazarian 2009). By varying δ we obtained a new outlook on the technique; in particular, we found that the dendrogram distribution and hierarchy have a strong dependency on the magnetization and compressibility of the gas and are sensitive to the amount of self-gravity.…”
Section: Discussionmentioning
confidence: 99%
“…This yields two distinct power laws, which we fit individually using the segmented linear model described in K16. The fit at larger scales describes bulk gas velocity-dominated motion; the fit at smaller scales describes gas density-dominated motions (Chepurnov & Lazarian 2009). Kowal et al (2007) find that the density-dominated regime is sensitive to the magnetic field strength, where stronger fields correspond to steeper slopes.…”
Section: Spatial Power Spectrummentioning
confidence: 99%